Genetic responses in sexual diploid and unisexual triploid goldfish (Carassius auratus) introduced into a high‐altitude environment. Issue 8 (10th February 2023) - Feng, Xiu; Liu, Shenglin; Sui, Xiaoyun; Chen, Yifeng; Zhu, Ren; Jia, Yintao; Tong, Jingou; Yu, Xiaomu; Liu, Chunlong; Hansen, Michael M.
Abstract: Anthropogenic biological invasions represent major concerns but enable us to investigate rapid evolutionary changes and adaptation to novel environments. The goldfish Carassius auratus with sexual diploids and unisexual triploids coexisting in natural waters is one of the most widespread invasive fishes in Tibet, providing an ideal model to study evolutionary processes during invasion in different reproductive forms from the same vertebrate. Here, using whole‐genome resequencing data of 151 C. auratus individuals from invasive and native ranges, we found different patterns of genomic responses between diploid and triploid populations during their invasion of Tibet. For diploids, although invasive individuals derived from two different genetically distinct sources had a relative higher diversity (π) at the population level, their individual genetic diversity (genome‐wide observed heterozygosity) was significantly lower (21.4%) than that of source individuals. Population structure analysis revealed that the invasive individuals formed a specific genetic cluster distinct from the source populations. Runs of homozygosity analysis showed low inbreeding only in invasive individuals, and only the invasive population experienced a recent decline in effective population size reflecting founder events. For triploids, however, invasive populations showed no loss of individual genetic diversity and no genetic differentiation relative to source populations. Regions of putative selective sweeps between invasive and source populations of diploids mainly involved genes associated with mannosidase activity and embryo development. Our results suggest that invasive diploids deriving from distinct sources still lost individual genetic diversity resulting from recent inbreeding and founder events and selective sweeps, and invasive triploids experienced no change in genetic diversity owing to their reproduction mode of gynogenesis that precludes inbreeding and founder effects and may make them more powerful invaders.